Prostatectomy - Genadiev, Tsvetin (IntechOpen, 2019)
The prostate gland is one of the male organs that have changed over the years. Those changes lead to a disruption of the quality of life and risk of prostate cancer in men over 50 years of age. In the era of prostate-specific antigen it is possible to overcome prostate cancer through early diagnosis. This made it possible to treat the diagnosis of prostate cancer and prevent the development of prostate cancer disease in the patient. In addition, early diagnosis has led to advances in the technological development of the basic surgical technique - prostatectomy. This book contains the efforts of a number of doctors and scientists interested in the prostate gland from different countries around the world. Some of these studies are likely to pose new challenges and trends in the diagnosis of the prostate gland and basic surgical technique.